A polyglycolic acid composition with special microstructure and its preparation method and application

By preparing polyglycolic acid compositions with special microstructures, and using melt blending and extrusion processes to form a bicontinuous phase structure, the problems of easy degradation and poor stability of polyglycolic acid are solved, and the stability of material aging and shelf life are improved.

CN115850930BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211432863.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-03-04
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

Polyglycolic acid is easy to degrade, has poor long-term storage stability, and there is a problem of phase separation in PGA/PLA blends, which affects the aging stability of the material.

Method used

By preparing polyglycolic acid compositions with special microstructures, melt blending and extrusion processes are used to form a bicontinuous phase structure, which improves the aging stability of the high PGA content blend.

Benefits of technology

The aging stability of polyglycolic acid composition is improved, the shelf life and application cycle of the product are extended, and the problems of easy degradation and poor stability of PGA are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115850930B_ABST
    Figure CN115850930B_ABST
Patent Text Reader

Abstract

The present invention relates to a polyvinyl alcohol acid composition with a special microstructure in the field of polymer material modification and preparation, and a preparation method and application thereof. The polyglycolic acid composition comprises the following components by weight: (1) 85 to 99 parts of polyglycolic acid; (2) 1 to 15 parts of polylactic acid. Due to the special ratio and processing conditions of polyglycolic acid and polylactic acid, a polyglycolic acid composition with a special microstructure is obtained, and the structure has a significant effect on delaying the degradation of the polyglycolic acid composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a polyglycolic acid composition with a special microstructure, a preparation method and application thereof. Background Art

[0002] As the simplest linear aliphatic polyester, polyglycolic acid (PGA) is a typical high-crystallinity polymer with a stable lattice and a high melting point. In recent years, PGA has received extensive attention and application in the fields of medical sutures, drug controlled release carriers, fracture fixation materials, tissue engineering scaffolds, reinforcement materials, oil fields, etc. due to its excellent biodegradability, fast degradation rate, good biocompatibility, good bioresorbability, and high mechanical strength (some indicators are higher than engineering plastics). However, a series of problems such as high melting point, narrow processing temperature, high crystallinity, and fast degradation rate of PGA have seriously affected its processing and material application.

[0003] Polylactic acid (PLA) is a type of biodegradable polyester material mainly made from bio-based materials. It has the advantages of high rigidity and strength, good biocompatibility, and complete biodegradability. The PLA structure includes chiral carbon atoms, and there are two structures, left-handed and right-handed. Currently, the most commonly used is left-handed polylactic acid - PLLA. PLA is the first choice for reinforcing soft biodegradable materials due to its good performance and relatively low cost.

[0004] Since both PLA and PGA have excellent biocompatibility, degradability and mechanical rigidity, in recent years, a large number of researchers have used the composite of the two to replace metal materials in artificial bones, stents, and other biomedical fields. Although PGA and PLA have similar structures, Qiao Hu et al. (Engineering Plastics Applications, 2020, 48(1): 8-12.) found that the blend of the two is a thermodynamically incompatible system. The addition of chain extenders can improve compatibility to a certain extent, but there is still obvious phase separation. Therefore, there are still certain problems in the application of PGA / PLA blends. Current studies have found that the degradation rate of PLA is much lower than that of PGA, that is, PLA has better stability. Therefore, in the application of PGA / PLA blends and their products, PLA is often still used as the main phase to obtain a longer shelf life and stability. However, this will bring an upper limit to the amount of PGA added to the blend. Summary of the invention

[0005] One of the technical problems to be solved by the present invention is that polyglycolic acid in the prior art is easily degraded and has poor long-term storage stability.

[0006] The second technical problem to be solved by the present invention is to provide a method for preparing the polyglycolic acid composition having a special microstructure.

[0007] The third technical problem to be solved by the present invention is to provide a polyglycolic acid composition with a special microstructure prepared by the method for preparing a polyglycolic acid composition with a special microstructure.

[0008] The fourth technical problem to be solved by the present invention is to provide an application of a polyglycolic acid composition having a special microstructure corresponding to the first technical problem to be solved or the third technical problem to be solved.

[0009] In order to solve the above technical problems, the present invention proposes to prepare a PGA / PLA blend with a special microstructure based on the physical properties and process of PGA and PGA, hoping to improve the aging stability of a high PGA content PGA / PLA blend.

[0010] The first aspect of the present invention is to provide a polyglycolic acid composition with a special microstructure, wherein the polyglycolic acid composition comprises polyglycolic acid and polylactic acid, and in the microstructure of the polyglycolic acid composition, the polyglycolic acid phase and the polylactic acid phase are both continuous phases.

[0011] According to an embodiment of the present invention, in the polyglycolic acid composition, the length of the polyglycolic acid phase or the polylactic acid phase is greater than its width. Preferably, the length of the polyglycolic acid phase or the polylactic acid phase is at least 40 microns, preferably 40 to 150 microns; the width of the polyglycolic acid phase or the polylactic acid phase is 5 to 30 microns, preferably 5 to 20 microns.

[0012] According to an embodiment of the present invention, based on 100 parts by total weight of the polyglycolic acid composition, it comprises 85 to 99 parts of polyglycolic acid and 1 to 15 parts of polylactic acid; for example, the polyglycolic acid can be 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98 or 99 parts, or a numerical range between any two of the above values; the polylactic acid can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 parts, or a numerical range between any two of the above values; preferably, based on 100 parts by total weight of the polyglycolic acid composition, it comprises 85 to 95 parts of polyglycolic acid and 5 to 15 parts of polylactic acid.

[0013] According to an embodiment of the present invention, the polyglycolic acid can be prepared by ring-opening polymerization of glycolide or condensation polymerization of glycolic acid or methyl glycolate; preferably, the polyglycolic acid has a crystallinity of 10 to 60%; for example, the crystallinity can be 10%, 20%, 30%, 40%, 50%, 60% or a numerical range between any two of the above values; the intrinsic viscosity of the polyglycolic acid can be 0.9 to 1.8 dl / g, for example, the intrinsic viscosity can be 0.9 dl / g, 1.0 dl / g, 1.1 dl / g, 1.2 dl / g, 1.3 dl / g, 1.4 dl / g, 1.5 dl / g, 1.6 dl / g, 1.7 dl / g, 1.8 dl / g or a numerical range between any two of the above values, and more preferably 0.9 to 1.4 dl / g.

[0014] According to an embodiment of the present invention, the polylactic acid is formed by ring-opening condensation of lactide or by direct polymerization of lactic acid, and is preferably formed by ring-opening condensation of lactide; preferably, the polylactic acid has a melt index of 1 to 50 g / 10 min under test conditions of 190°C and 2.16 kg, for example, the melt index may be 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min or a numerical range between any two of the above values, and may further preferably be 20 to 40 g / 10 min.

[0015] According to an embodiment of the present invention, the polyglycolic acid composition with a special microstructure is prepared by melt extrusion of polyglycolic acid and polylactic acid. In the present invention, polyglycolic acid and polylactic acid with appropriate proportions can form a special microstructure under the action of shear force under specific melt extrusion conditions. Preferably, the polyglycolic acid composition with a special microstructure provided by the present invention has a melt flow rate of 1 to 200 g / 10 min, preferably 10 to 140 g / 10 min, under the test conditions of 230°C and 2.16 kg.

[0016] The second aspect of the present invention is to provide a method for preparing the polyglycolic acid composition, comprising: preparing the polyglycolic acid composition by melt blending and extruding components including the polyglycolic acid and polylactic acid.

[0017] According to an embodiment of the present invention, the polyglycolic acid and polylactic acid are fully dried before use. The specific drying operation can be completed by using the drying equipment and process conditions commonly used in the art. For example, a blast oven or a vacuum oven can be used. Preferably, the drying conditions are: the drying temperature is 40 to 150°C, preferably 60 to 110°C; the drying time is 1 to 8 hours, preferably 3 to 5 hours. For example, the drying temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or a numerical range between any two of the above values, and the drying time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or a numerical range between any two of the above values.

[0018] According to an embodiment of the present invention, melt blending can be performed using a commonly used blending device in the art, such as an internal mixer, a single-screw extruder, a twin-screw extruder, and other processing equipment, preferably a twin-screw extruder; more preferably,

[0019] The conditions for melt blending are: screw length-diameter ratio ≥ 16:1, shear rate 10-5000s -1 , the shear temperature is 180-300°C; preferably, the screw aspect ratio is ≥32:1, and the shear rate is 1000-2000s -1 , the shear temperature is 200~230℃; for example,

[0020] The extrusion conditions are: multi-temperature zone extrusion (for example, at least 4 temperature zones), the extrusion temperature is 190-260°C and the temperature of at least two temperature zones is 230°C, preferably, the extrusion temperature is 210-250°C and the temperature of at least two temperature zones is 230°C; the speed of the extruder is 50-500rpm, preferably 60-250rpm; for example, the extrusion temperature can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or any two of the above values The speed of the extruder may be 50rpm, 60rpm, 70rpm, 80rpm, 90rpm, 100rpm, 120rpm, 150rpm, 170rpm, 180rpm, 200rpm, 220rpm, 240rpm, 250rpm, 260rpm, 270rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm or a numerical range between any two of the above values.

[0021] The third aspect of the present invention is to provide a polyglycolic acid composition extrusion material, comprising the polyglycolic acid composition with a special microstructure or the polyglycolic acid composition with a special microstructure obtained by the above preparation method.

[0022] According to an embodiment of the present invention, the polyglycolic acid composition extrusion material can be obtained by an extrusion process commonly used in the art. Preferably, the polyglycolic acid composition extrusion material provided by the present invention has a tensile strength retention rate of at least 14% after 21 days of ultraviolet radiation accelerated aging.

[0023] The fourth aspect of the present invention is to provide the use of the polyglycolic acid composition with a special microstructure or the extruded material of the polyglycolic acid composition in the preparation of injection molded parts, films, and spinning. The application is not particularly limited, including but not limited to a wide range of applications in medicine, daily necessities, oil production, etc.

[0024] The materials and preparation methods used in the present invention are briefly introduced as follows:

[0025] 1. Polyglycolic acid

[0026] Polyglycolic acid (PGA), also known as polyglycolic acid, is the simplest thermoplastic linear aliphatic polyester. PGA can be prepared by methods such as glycolic acid melt polycondensation or glycolide ring-opening polymerization. Polyglycolic acid is a typical high-crystalline polymer with a stable lattice and a high melting point. PGA is a type of hydrophilic resin, and its surface is easily hygroscopic and hydrolyzed and aged, so its product stability is poor, which limits its application.

[0027] Polyglycolic acid has excellent biodegradability. It can enter the human circulatory system to be degraded in the body and excreted from the body. It can also be degraded in the in vitro environment. It is mainly used in medical sutures, drug controlled release carriers, fracture fixation materials, tissue engineering scaffolds, reinforcement materials, etc. Through solution spinning and melt spinning, polyglycolic acid can be processed into surgical sutures with strong tensile strength and can maintain sufficient time, which is suitable for suturing deep tissue wounds.

[0028] 2. Polylactic acid

[0029] Polylactic acid (PLA) is an important lactic acid derivative product. It is a polyester material that is non-toxic and harmless to the human body. It is a biodegradable polymer material chemically synthesized from lactic acid monomers. At present, PLA can be obtained by direct polycondensation of lactic acid (PC method) or ring-opening polymerization of lactide (ROP method). Among them, the PC method includes melt polycondensation, melt polycondensation-solid phase polymerization, and solution polycondensation. In comparison, the ROP method can obtain polylactic acid with a relatively high molecular weight. Polylactic acid has good biocompatibility, biodegradability, and non-toxicity. It is often used in medicine as surgical sutures that do not require suture removal, bone repair materials, drug controlled release materials, artificial bones, etc.

[0030] Polylactic acid is a biodegradable polymer with good toughness. It can be directly processed and molded by extrusion, injection molding, spinning blow molding and other processes through general plastic processing equipment. It is currently widely used in agricultural mulch films, agricultural and sideline product packaging bags, fast food boxes, disposable knives and forks and other fields.

[0031] 3. Polyglycolic acid and polylactic acid composition

[0032] In the method for preparing the polyglycolic acid / polylactic acid composition, melt blending reaction extrusion is adopted to uniformly mix the required amounts of the components in a molten state to obtain the polyglycolic acid / polylactic acid composition with high toughness.

[0033] One specific embodiment is that polyglycolic acid and polylactic acid are metered and added to a twin-screw extruder according to a certain feeding ratio for melt blending, extrusion and granulation. Another specific embodiment is that polyglycolic acid and polylactic acid are blended according to a required ratio and then added to a twin-screw extruder for melt blending, extrusion and granulation.

[0034] In the step of preparing the polyglycolic acid / polylactic acid composition, the extrusion temperature suitable for the present invention may be 200 to 260° C., preferably 220 to 250° C. The rotation speed of the extruder is preferably 50 to 500 rpm, more preferably 60 to 250 rpm.

[0035] The present invention provides a polyglycolic acid composition with a special microstructure and a preparation method thereof. After melt blending, extrusion, cooling and granulation, the obtained polyglycolic acid / polylactic acid blend particles have a unique phase structure. The structure is a special microstructure, that is, PGA and PLA do not form a conventional sea island phase-ocean phase microstructure (the one with a high content is the ocean phase), but unexpectedly form a special microphase structure of a dual continuous phase. In this way, the negative impact of excessive aging and degradation of PGA (high content) on the overall mechanical properties of the PGL / PLA composite material and the resulting short shelf life that does not meet the use requirements are creatively solved. Under the high PGA content of the present invention, PLA unexpectedly forms a continuous phase structure, that is, the surface contains PLA with a slower degradation rate, so it can better alleviate and improve the aging stability of the product, and extend the product shelf and applicable cycle. After 3 weeks of accelerated aging with a xenon lamp, the tensile strength retention rate of the sample made by injection molding of the composition is greater than 35%, which can solve the problem of easy degradation and poor long-term storage stability of polyglycolic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figures 1 to 6 The cross-sectional SEM micromorphologies of the PGA / PLA compositions obtained in Example 1 and Comparative Examples 1 to 5 are shown respectively. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] Source of raw materials

[0040] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0041] The raw materials used in the examples and comparative examples are all commercially available.

[0042] Polyglycolic acid (PGA), produced by Corbion Purac, has an intrinsic viscosity of 1.0-1.4 dl / g; a melt flow rate of 41 g / 10 min at 230°C and 2.16 kg; a melting range of 200-230°C and a crystallinity of 41% when tested at a heating / cooling rate of 10°C / min;

[0043] Polylactic acid (PLA), the grade produced by NatureWorks is 3251D. When tested at a heating / cooling rate of 10°C / min, the melting range is 150-170°C; the melt index at 190°C and 2.16kg is 35g / 10min.

[0044] The present invention performs performance measurement according to the following method:

[0045] Phase structure characterization: A German ZEISS MERLIN scanning electron microscope (SEM) was used to observe the cross section of the PGA / PLA blend material after liquid nitrogen quenching.

[0046] Xenon lamp aging performance test: carried out in the Q-Sun Xe-3-HS xenon lamp accelerated aging test chamber of Q-Lab, USA. ISO 4892-2 standard is adopted, and the light intensity at 340nm wavelength under the daylight filter is 0.51W / (m 2·nm), the blackboard temperature was 65℃, the box temperature was 38℃, the relative humidity was 50%, and a test cycle was 120 minutes, of which 102 minutes were dry light exposure and the other 18 minutes were light exposure plus pure water spraying.

[0047] [Comparative Example 1]

[0048] 8 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 92 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 225℃, 235℃, 235℃, 235℃, 235℃, 230℃, 225℃ and 215℃, respectively, and the screw speed is set to 67rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, dried in a vacuum oven at 60℃ for 4h, and then packaged for use.

[0049] [Comparative Example 2]

[0050] 5 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 95 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 225℃, 235℃, 235℃, 235℃, 235℃, 230℃, 225℃ and 215℃, respectively, and the screw speed is set to 67rpm. During stable operation, the torque range is 25-35%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0051] [Comparative Example 3]

[0052] 8 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 92 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 225℃, 235℃, 235℃, 235℃, 235℃, 230℃, 225℃ and 215℃, respectively, and the screw speed is set to 135rpm. During stable operation, the torque range is 20-40%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0053] [Comparative Example 4]

[0054] 13 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 87 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 225℃, 235℃, 235℃, 235℃, 235℃, 230℃, 225℃ and 215℃, respectively, and the screw speed is set to 202rpm. During stable operation, the torque range is 20-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0055] [Comparative Example 5]

[0056] 20 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 80 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 225℃, 235℃, 235℃, 235℃, 235℃, 230℃, 225℃ and 215℃, respectively, and the screw speed is set to 230rpm. During stable operation, the torque range is 20-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, dried in a vacuum oven at 60℃ for 4h, and then packaged for use.

[0057] [Example 1]

[0058] 5 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 95 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 220℃, 230℃, 230℃, 230℃, 230℃, 225℃, 220℃ and 210℃, respectively, and the screw speed is set to 67rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, dried in a vacuum oven at 60℃ for 4h, and then packaged for use.

[0059] [Example 2]

[0060] 6 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 94 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 220℃, 230℃, 230℃, 230℃, 230℃, 225℃, 220℃ and 210℃, respectively, and the screw speed is set to 67rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, dried in a vacuum oven at 60℃ for 4h, and then packaged for use.

[0061] [Example 3]

[0062] 7 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 93 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 220℃, 230℃, 230℃, 230℃, 230℃, 225℃, 220℃ and 210℃, respectively, and the screw speed is set to 67rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, dried in a vacuum oven at 60℃ for 4h, and then packaged for use.

[0063] [Example 4]

[0064] 9 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 91 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 220℃, 230℃, 230℃, 230℃, 230℃, 225℃, 220℃ and 210℃, respectively, and the screw speed is set to 135rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, dried in a vacuum oven at 60℃ for 4h, and then packaged for use.

[0065] [Example 5]

[0066] 15 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 85 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 220℃, 230℃, 230℃, 230℃, 230℃, 225℃, 220℃ and 210℃, respectively, and the screw speed is set to 202rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0067] [Example 6]

[0068] 13 parts by weight of fully dried polylactic acid (NatureWorks, 3251D) and 87 parts by weight of PGA (Corbion Purac, melt flow rate 41 g / 10 min) were fully premixed and added to the mixture through a feeder. TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200℃, 200℃, 220℃, 230℃, 230℃, 230℃, 230℃, 225℃, 220℃ and 210℃, respectively, and the screw speed is set to 202rpm. During stable operation, the torque range is 30-50%. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles of about 3mm by a pelletizer. The particles are collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0069] After quenching in liquid nitrogen, the six PGA / PLA blends of Example 1 and Comparative Examples 1 to 5 were subjected to gold spraying and then observed on a German ZEISS MERLIN scanning electron microscope (SEM). The cross-sectional microstructures obtained were as follows: Figure 1-Figure 6 And as shown in Table 1.

[0070] Table 1

[0071] Sample PGA / PLA Screw speed / rpm Temperature / ℃ Microstructure type Example 1 95 / 5 67 230 Dual continuous phase Example 2 94 / 6 67 230 Dual continuous phase Example 3 93 / 7 67 230 Dual continuous phase Example 4 91 / 9 135 230 Dual continuous phase Example 5 85 / 15 202 230 Dual continuous phase Example 6 87 / 13 202 230 Dual continuous phase Comparative Example 1 94 / 6 67 235 Island-ocean facies Comparative Example 2 95 / 5 67 235 Island-ocean facies Comparative Example 3 92 / 8 135 235 Island-ocean facies Comparative Example 4 87 / 13 202 235 Island-ocean facies Comparative Example 5 80 / 20 230 235 Island-ocean facies

[0072] From the results, it can be seen that Examples 1 to 6 formed a relatively obvious dual-continuous phase structure (such as Figure 1 As shown), the length of the polyglycolic acid phase or polylactic acid phase is about 50 microns, and the width of the polyglycolic acid phase or polylactic acid phase is about 10 microns. Comparative Examples 1 to 5 form a conventional island phase structure. It can be seen from Example 1 and Comparative Example 2, Example 2 and Comparative Example 1, and Example 6 and Comparative Example 4 that under the same PGA / PLA composition and screw speed, different temperatures are extremely sensitive to the microscopic phase structure of the PGA / PLA composition, and the dual continuous phase can only be formed at 230°C. When the screw speed is 67rpm and the screw temperature is 230°C, the PLA content in the composition is 5-7% to form a dual continuous phase. When the screw speed is 202rpm, the screw temperature is 230°C, and the PLA content in the composition is 13-15%, a dual continuous phase can be formed. The PGA / PLA composition is extremely sensitive to processing temperature and screw speed. Only when specific process and composition conditions are met can a special microstructure be formed; under other composition and process conditions, only a microscopic phase structure with PGA marine phase and PLA as island phase can be obtained.

[0073] [Example 7] Preparation and testing of polyglycolic acid composition extrusion materials

[0074] A total of 11 particles of Examples 1 to 6 and Comparative Examples 1 to 5 were dried at 100°C for 3 hours. TM Injection molding was performed in a MiniJet II micro injection molding machine. The mold was a 557-2295-60×10×1 mold produced by Thermo Fisher Technology. During the experiment, the cavity temperature and mold temperature were set to 230°C and 60°C, respectively. During the injection molding process, the pressure was set to 300 bar for 5 seconds, and the subsequent holding pressure process was 100 bar for 10 seconds, after which the mold was demolded and the injection molded specimens were collected.

[0075] Next, the above 6 injection molded specimens were placed in the Q-Sun Xe-3-HS xenon lamp accelerated aging test chamber of Q-Lab Company in the United States for xenon lamp accelerated aging test. Samples were taken at 0, 7, 14 and 21 days to test the mechanical properties of the injection molded specimens. The relationship between the mechanical strength of the PGA / PLA composite specimens under different compositions and the aging time was obtained.

[0076] Table 2. Tensile strength retention rate of comparative examples and example strips at different aging times (%)

[0077]

[0078] From the aging test results, it can be seen that compared with the PGA / PLA strips (comparative example) with the ordinary island-ocean phase structure, only when the PGA / PLA strips present a bicontinuous special microstructure (Examples 1-6), after 21 days of accelerated aging, they have the highest tensile strength retention rate (39.7-40.6%, see Table 2), while the tensile strength retention rate of the comparative example with the island-ocean phase structure is only 13.2-35.2%. Therefore, the PGA blend with a bicontinuous phase special microstructure has excellent aging stability and prolongs the shelf life of the product, which will greatly promote the wide application of PGA in the field of injection molding products.

Claims

1. A polyglycolic acid composition having a special microstructure, wherein the polyglycolic acid composition comprises polyglycolic acid and polylactic acid, and in the microstructure of the polyglycolic acid composition, both the polyglycolic acid phase and the polylactic acid phase are continuous phases; based on 100 parts by total weight of the polyglycolic acid composition, the polyglycolic acid composition comprises 85 to 99 parts by weight of polyglycolic acid and 1 to 15 parts by weight of polylactic acid; The polyglycolic acid composition is prepared by melt blending and extruding the components including the polyglycolic acid and polylactic acid; wherein, The conditions for melt blending are: screw length-diameter ratio ≥ 16:1, shear rate 10-5000s -1 , the shear temperature is 180-300°C; the extrusion conditions are: multi-temperature zone extrusion, the extrusion temperature is 190-260°C and the temperature of at least two temperature zones is 230°C; The length of the polyglycolic acid phase or polylactic acid phase is greater than its width. The length of the polyglycolic acid phase or polylactic acid phase is at least 40 microns, and the width of the polyglycolic acid phase or polylactic acid phase is 5 to 30 microns.

2. The polyglycolic acid composition according to claim 1, characterized in that The length of the polyglycolic acid phase or the polylactic acid phase is 40 to 150 microns; the width of the polyglycolic acid phase or the polylactic acid phase is 5 to 20 microns.

3. The polyglycolic acid composition according to claim 1, characterized in that Based on 100 parts by total weight of the polyglycolic acid composition, the polyglycolic acid composition comprises 85 to 95 parts by weight of polyglycolic acid and 5 to 15 parts by weight of polylactic acid.

4. The polyglycolic acid composition according to claim 1, characterized in that The polyglycolic acid has a crystallinity of 10 to 60%; and / or, The intrinsic viscosity of the polyglycolic acid is 0.9 to 1.8 dl / g; and / or, The polylactic acid has a melt index of 1 to 50 g / 10 min under the test conditions of 190° C. and 2.16 kg.

5. The polyglycolic acid composition according to claim 4, characterized in that The intrinsic viscosity of the polyglycolic acid is 0.9 to 1.4 dl / g; and / or, The polylactic acid has a melting index of 20 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg.

6. The polyglycolic acid composition according to any one of claims 1 to 5, characterized in that The polyglycolic acid composition has a melt flow rate of 1 to 200 g / 10 min under the test conditions of 230° C. and 2.16 kg.

7. The polyglycolic acid composition according to claim 6, characterized in that The polyglycolic acid composition has a melt flow rate of 10 to 140 g / 10 min under the test conditions of 230° C. and 2.16 kg.

8. A method for preparing the polyglycolic acid composition having a special microstructure according to any one of claims 1 to 7, comprising: The polyglycolic acid composition is prepared by melt blending and extruding the components including the polyglycolic acid and polylactic acid.

9. The preparation method according to claim 8, characterized in that: The polyglycolic acid and polylactic acid are dried before use; and / or, The melt blending adopts a twin-screw extruder.

10. The preparation method according to claim 9, characterized in that: The drying conditions are: drying temperature of 40 to 150°C; drying time of 1 to 8 hours; and / or, The conditions for melt blending are: screw length-diameter ratio ≥ 16:1, shear rate 10-5000s -1 , the shear temperature is 180 to 300°C; and / or, The extrusion conditions are: multi-temperature zone extrusion, the extrusion temperature is 190-260° C. and the temperature of at least two temperature zones is 230° C.; the rotation speed of the extruder is 50-500 rpm.

11. The preparation method according to claim 10, characterized in that: The drying conditions are: drying temperature is 60-110°C; drying time is 2-4 hours; and / or, The conditions for melt blending are: screw aspect ratio ≥32:1, shear rate 1000~2000s -1 , the shear temperature is 200 to 230°C; and / or, The extrusion conditions are as follows: the extrusion temperature is 210-250° C., and the temperature of at least two temperature zones is 230° C.; and the rotation speed of the extruder is 60-250 rpm.

12. A polyglycolic acid composition extrusion material, comprising the polyglycolic acid composition with a special microstructure according to any one of claims 1 to 7 or the polyglycolic acid composition with a special microstructure obtained by the preparation method according to any one of claims 8 to 11.

13. The polyglycolic acid composition extrusion material according to claim 12, characterized in that: The retention rate of the tensile strength of the polyglycolic acid composition extrusion material is at least 14% after 21 days of ultraviolet radiation accelerated aging.

14. Use of the polyglycolic acid composition with a special microstructure according to any one of claims 1 to 7 or the extruded material of the polyglycolic acid composition according to any one of claims 12 to 13 in injection molding, film, and spinning.

Citation Information

Patent Citations

  • Coupling and capacity increasing technique for coblended interface of biodegradation polylactic acid / starch composite material

    CN101367986A

  • Special starch / PLA-PGA-PBAT biodegradable compostable material and preparation method thereof

    CN113429764A

  • Toughening degradable polyglycolic acid composition, and toughening degradable polyglycolic acid material and preparation method therefor and use thereof

    WO2022037349A1